From healthy education to a healthy population: testing the impact of the innovative school health program on health of primary school students in Azerbaijan - Suleymanova, Afet; Bashirova, Elnara (Springer Netherlands rbk@louisiana.edu, 2018)
Studies by many researchers show that hypodynamia, insufficient nutrition, stress, and other malicious habits create serious problems for the health of children and adolescents. Physical and mental health promotion among children in schools and thereby improvement of their learning achievements is a novel idea which is a focus of doctors, psychologists, and teachers as educators. Experts point out that most of the primary school children spend 25% of their awake time, daily on average, sitting down in class and after school. Inadequate environment and climate in schools lead to limited mobility, physical disability, visual disturbances and other health problems among children. Some studies reveal that only 2–15% of graduates of general schools are fully healthy. Over the past decade, some state programs have been adopted in different countries to address these problems. This paper reports on a 4-year follow-up data—from 2013 to 2017 inclusively—collected from the healthy life style education adopted in primary schools of Azerbaijan Republic; and it analyses the outcomes. © 2017, Springer Science+Business Media B.V., part of Springer Nature.
Keywords: Classroom environment; Healthy educational technologies; Learning achievement; Quality